A meta-analysis of published data on the efficacy and safety of radiotherapy combined with systemic therapy in advanced esophageal carcinoma - Chen, Xiaoxi; Cheng, Rutian; Liu, Shuang; Cao, Yu; Liu, Lihong; Dong, Hua; Ren, Xuejiao; Liu, Shutang; Li, Xiaoning; Han, Chun; Wang, Lan (Frontiers in Oncology, 2026)
IntroductionChemoimmunotherapy or chemotherapy-based drug therapy is the preferred treatment for advanced esophageal cancer. However, the prognosis of patients is poor, there is an urgent need to explore more effective combined treatment strategies to improve survival outcomes. In this study, we conducted a meta-analysis to evaluate the efficacy and safety of combined treatment with chemoimmunotherapy or chemotherapy and radiotherapy.MethodsPubMed, Embase, Web of Science, Cochrane Library and China National Knowledge Infrastructure (CNKI) were searched using a combination of subject terms and free words. Data were extracted from studies that met the inclusion criteria and meta-analyzed using Stata 17.0 software to compare the efficacy and treatment-related adverse toxicities of chemotherapy/chemoimmunotherapy plus radiotherapy with chemotherapy/chemoimmunotherapy alone.ResultsFinally, a total of 12 studies (11 retrospective cohort studies and 1 randomized controlled trial) involving 2,428 patients were included in the analysis, with squamous cell carcinoma accounting for 98.9%. In terms of efficacy, meta-analysis revealed the radiotherapy combined group (RT group) had significantly higher objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS) than those of the non-radiotherapy combined group (NRT group). Stratified analysis showed that for patients with immune checkpoint inhibitors (ICIs)-based systemic treatment and oligometastatic esophageal cancer, the OS and PFS of the RT group were significantly better than those of the NRT group (ICIs ± radiotherapy: Hazard ratio (HR)=0.61, 95%CI:0.48-0.76, P<0.001; HR = 0.60, 95%CI:0.49-0.73, P<0.001, oligometastatic esophageal cancer: HR = 0.73, 95% CI: 0.64-0.84, P<0.001; HR = 0.66, 95% CI: 0.58-0.76, p<0.001). The incidence of grade≥3 hematological toxicity and treatment-related pneumonia in the RT group was higher than that in the NRT group, and there was no significant difference in gastrointestinal adverse reactions between the two groups(2.5%-12.2% vs. 3.4%-13.2%, P = 0.828).ConclusionsBased on the current data, systemic therapy combined with local radiotherapy may be a better option for advanced esophageal cancer, but the potential risk of higher hematological toxicity and treatment-related pneumonia need to be weighed.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, PROSPERO identifier CRD420251101459.